Encyclopedia of Chemistry Laboratory Equipment to Support Basic Chemistry Practicum Learning - I Ketut Sudiana (Universitas Pendidikan Ganesha, 2022)
First-year students experience problems carrying out Basic Chemistry practicums due to shared knowledge and skills in chemical laboratory equipment. These conditions can hinder the achievement of practicum objectives and potentially cause work accidents. This study aims to produce an Encyclopedia of Chemistry Laboratory Equipment to support Basic Chemistry Practicum Learning. This research is a Research and Development (R&D) with a 4-D development model. The method used to collect data is observation, interviews, and questionnaires. The instrument used to collect data is a test sheet. The data analysis technique used is descriptive qualitative, and quantitative analysis. The results of the research are expert judgments. The results show that the Encyclopedia of Basic Chemistry Laboratory Tools is very valid in terms of content (3.86), language (3.94), media (3.86), and video (3.7) from a maximum score of 4. The readability test results of 9 students showed that all students gave a precise assessment. They clearly understand the information about laboratory equipment used as an entry in the Encyclopedia of chemical laboratory equipment. This study concludes that the Encyclopedia of Chemistry Laboratory Tools is feasible to implement the content, language, media, video, and readability to support learning Basic Chemistry Practicum.